Implementation of the Tahfidz Quran Program in Developing Islamic Character - Najiburrahman Najiburrahman; Yunita Noor Azizah; Jazilurrahman Jazilurrahman; Wafiq Azizah; Nur Aisyatul Jannah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The purpose of the study was to examine the implementation of the Tahfidz Qur'an program in developing Islamic character in Masyithoh Sukodadi Kindergarten (TK) Paiton Probolinggo. This type of research is qualitative with a phenomenological approach. The research subjects were teachers, principals and students at Masyithoh Kindergarten. Methods of data collection using interviews, observation and documentation. Data analysis uses the Constant Comparative Analysis model with three processes, namely open coding, axial coding and selective coding. The results of the field research obtained findings of the implementation of the Tahfidz Qur'an program in developing Islamic character in Masyithoh Kindergarten (TK) namely the preparation, planning, and implementation of the program. While the implications of the Qur'an tahfidz program in developing Islamic character in Masyithoh Kindergarten through the achievement of forming 4 characters, namely: religious, disciplined, patient and istiqomah